Synthesis, electronic properties and self-assembly on Au{111} of thiolated (oligo)phenothiazines - Franz, Adam W.; Stoycheva, Svetlana; Himmelhaus, Michael; Müller, Thomas J. J. (Beilstein journal of organic chemistry, 2010)
Beilstein Journal of Organic Chemistry
Gesehen am 18.12.2023